Enhanced properties of well-defined polymer networks prepared by a sequential thiol-Michael - radical thiol-ene (STMRT) strategy. (15th May 2021) - Cespedes, Sergio; Hand, Rachel A.; Chmel, Nikola; Moad, Graeme; Keddie, Daniel J.; Schiller, Tara L.
Graphical abstract: Highlights: STMRT, a new strategy for the synthesis of thiol-acrylate-vinyl ether networks. Base catalysed Thiol-Michael and radical thiol-ene successfully combined. Fine tuning of Tg by selection of PEGDA chain length. Abstract: A sequential thiol-Michael - radical thiol-ene (STMRT) strategy was used to produce poly(ethylene glycol)-based model networks and enable establishment of a structure–property relationship from the network characteristics. Selective double thiol-Michael reactions on a series of poly(ethylene glycol) diacrylates (PEGDA), that differed in average chain length, with two molar equivalents of the trithiol trimethylolpropane tris(3-mercaptopropionate) (TMPTMP) yielded well-defined telechelic poly(ethylene glycol)-based tetrathiols. These tetrathiols were in turn used to produce model (co–)networks by photo-induced radical thiol-ene polymerization with either the same poly(ethylene glycol) diacrylates or with tri(ethyleneglycol) divinylether (TEGDVE). The properties of these networks were studied by Fourier transform infrared spectroscopy (FTIR), differential scanning calorimetry (DSC) and dynamic mechanical analysis (DMA). The STMRT-produced model networks possess storage moduli ( E ′) up to 4-fold larger and glass transition temperatures ( T g ) of up to 10 °C lower than conventionally produced counterparts. The STMRT strategy allows the properties of the model networks to be finely tuned by manipulation of crosslink density and average polymer chain length.